Cross-species comparison of AlphaFold-derived G protein-coupled receptor structures reveals novel melatonin-related receptor in Neurospora crassa. - Cathryn S D Maienza; Guillaume Lamoureux; Kwangwon Lee (PLoS ONE)
Melatonin, a molecule with diverse biological functions, is ubiquitously present in living organisms. There is significant interest in understanding melatonin signal transduction pathways in humans, particularly due to its critical role in regulating the sleep-wake cycle. However, a knowledge gap remains in fully elucidating the mechanisms by which melatonin influences circadian regulation. To bridge this gap, there is a growing need for a model system to study the role of melatonin in circadian clocks, with Neurospora crassa being a promising candidate. As a first step in this investigation, we focused on identifying melatonin receptors in N. crassa. Given the lack of sequence similarity between potential receptors in this fungus and known human melatonin receptors, we utilized structural similarity analysis through AlphaFold2. This approach led to the identification of a strong candidate gene, gpr-3, which shares structural similarities with human melatonin receptors. Experimental validation confirmed that the removal of GPR-3 from cells results in the absence of melatonin signaling. This proof-of-concept study underscores the potential of N. crassa as a model organism for circadian research and demonstrates the broader applicability of using AlphaFold2, especially when sequence similarity does not lead to candidate genes, for identifying novel receptors across different species.